Coaliciones fantasmas, esencialismos políticos y corrupción - Burbano de Lara, Felipe (2005)
This article reflects upon the trend of the Ecuadorian political parties of hiding their pacts and agreements. It sustains that the functioning of the "phantom coalitions" -as they have been defined by the politologist Andrés Mejía- should be explained in the necessity of the parties and their leaders, of maintaining, in the public scenario, identities that confirm the political legitimation and irreductible ethic values. The political negotiations and the agreements with the government, all inevitable in a democracy, are understood as irretrievable damages to the political identity, as unacceptable merge according to the point of view of the public image. Thus, these pacts should be hidden, denied, done under the table, eventhough the daily practice obliges to look for them constantly.